Decoding the morphological diversity in two dimensional crystalline porous polymers - Halder, Arjun; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Density functional calculations; Morphology

Self-templated chemically stable hollow spherical covalent organic framework - Kandambeth, Sharath; Venkatesh, V.; Shinde, Digambar B.; Kumari, Sushma; Halder, Arjun; Verma, Sandeep; Banerjee, Rahul (Nature Communications, 2015)
Covalent organic frameworks are a family of crystalline porous materials with promising applications. Although active research on the design and synthesis of covalent organic frameworks has been ongoing for almost a decade, the mechanisms of formation of covalent organic frameworks crystallites remain poorly understood. Here we report the synthesis of a hollow spherical covalent organic framework with mesoporous walls in a single-step template-free method. A detailed time-dependent study of hollow sphere formation reveals that an inside-out Ostwald ripening process is responsible for the hollow sphere formation. The synthesized covalent organic framework hollow spheres are highly porous (surface area similar to 1,500m(2) g(-1)), crystalline and chemically stable, due to the presence of strong intramolecular hydrogen bonding. These mesoporous hollow sphere covalent organic frameworks are used for a trypsin immobilization study, which shows an uptake of 15.5 mu mol g(-1) of trypsin.

Decoding the morphological diversity in two dimensional crystalline porous polymers by core planarity modulation - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew A.; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Angewandte Chemie - International Edition, 2016)

Interlayer hydrogen-bonded covalent organic frameworks as high-performance supercapacitors - Halder, Arjun; Ghosh, Meena; Khayum, Abdul M.; Bera, Saibal; Addicoat, Matthew; Sasmal, Himadri Sekhar; Karak, Suvendu; Kurungot, Sreekumar; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) have emerged as promising electrode materials in supercapacitors (SCs). However, their insoluble powder-like nature, poor capacitive performance in pristine form, integrated with inferior electrochemical stability is a primary concern for their long-term use in electrochemical devices. Keeping this in perspective, herein we report a redox active and hydrogen bonded COF with ultrahigh stability in conc. H2SO4 (18 M), conc. HCl (12 M) and NaOH (9 M). The as-synthesized COF fabricated as thin sheets were efficiently employed as a free-standing supercapacitor electrode material using 3 M aq. H2SO4 as an electrolyte. Moreover, the pristine COF sheet showcased outstanding areal capacitance 1600 mF cm(-2) (gravimetric 169 F g(-1)) and excellent cyclic stability (>100 000) without compromising its capacitive performance or Coulombic efficiency. Moreover, as a proof-of-concept, a solid-state supercapacitor device was also assembled and subsequently tested.

Multistimuli-responsive interconvertible low-molecular weight metallohydrogels and the in situ entrapment of CdS quantum dots therein - Bera, Saibal; Chakraborty, Amit; Karak, Suvendu; Halder, Arjun; Chatterjee, Soumyajyoti; Saha, Subhadeep; Banerjee, Rahul (Chemistry of Materials, 2018)
Two low molecular weight metallohydrogels (ZALA and CALA) have been synthesized from an amino-acid based ligand precursor (LA) and two different metal salts [zinc acetate dihydrate (ZA) and cadmium acetate dihydrate (CA), respectively. These two hydrogels show a unique chemically stimulated interconversion to each other via a reversible gel-sol gel pathway. This programmable gel-sol reversible system satisfies logic operations of a basic Boolean logic (INHIBIT) gate. Also, these hydrogels can be degraded into different MOF phases at room temperature spontaneously or in the presence of chloride and bromide salts (NaCl and NaBr.). CdS quantum dots can be grown inside the CALA gel matrix (CdS@CALA) in the presence of small amount of Na2S. This CdS doped gel exhibits time dependent tunable emission (white to yellow to orange) as a consequence of a slow agglomeration process of the entrapped quantum dots inside the gel matrix. This luminescence property also reflects the corresponding gel derived MOFs (obtained either by self-degradation of CdS@CALA or via anion induction) as well. This, to the best of our knowledge, is probably the simplest way to make a CdS quantum dot based composite material where CdS is entrapped within the gel and the gel-derived MOF matrix.

Superprotonic conductivity in flexible porous covalent organic framework membranes - Banerjee, Rahul; Sasmal, Himadri Sekhar; Harshitha, B. A.; Bhange, Siddheshwar; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar (Angewandte Chemie, 2018)
Poor mechanical stability of the polymer electrolyte membranes (PEMs) remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded covalent organic framework membranes (COFMs) showing the highest proton conductivity amongst all crystalline porous organic polymeric materials reported till date, as high as 7.8 x 10‐2 S cm‐1, have been further tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm‐2 power density, which is the highest among COFs and MOFs, highlights the possibilityof using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.

Ultrastable imine-based covalent organic frameworks for sulfuric acid recovery: an effect of interlayer hydrogen bonding - Halder, Arjun; Karak, Suvendu; Addicoat, Matthew; Bera, Saibal; Chakraborty, Amit; Kunjattu, Shebeeb H.; Pachfule, Pradip; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2018)
A rapid and scalable synthesis of six new imine-linked highly porous and crystalline COFs is presented that feature exceptionally high chemical stability in harsh environments including conc. H2SO4 (18M), conc. HCl (12M), and NaOH (9M). This is because of the presence of strong interlayer C-H center dot center dot center dot N hydrogen bonding among the individual layers, which provides significant steric hindrance and a hydrophobic environment around the imine (-C=N-) bonds, thus preventing their hydrolysis in such an abrasive environment. These COFs were further converted into porous, crystalline, self-standing, and crack-free COF membranes (COFMs) with extremely high chemical stability for their potential applications for sulfuric acid recovery. The as-synthesized COFMs exhibit unprecedented permeance for acetonitrile (280 Lm(-2) h(-1) bar(-1)) and acetone (260 Lm(-2) h(-1) bar(-1)).

Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.

Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching

Weak intermolecular interactions in covalent organic framework-carbon nanofiber based crystalline yet flexible devices - Mohammed, Abdul Khayum; Vijayakumar, Vidyanand; Halder, Arjun; Ghosh, Meena; Addicoat, Matthew; Bansode, Umesh; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2019)
<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">The redox-active and porous structural backbone of covalent organic frameworks (COFs) can facilitate high-performance electrochemical energy storage devices. However, the utilities of such 2D materials as supercapacitor electrodes in advanced self-charging power-pack systems have been obstructed due to the poor electrical conductivity and subsequent indigent performance. Herein, we report an effective strategy to enhance the electrical conductivity of COF thin sheets through the in situ solid-state inclusion of carbon nanofibers (CNF) into the COF precursor matrix. The obtained COF-CNF hybrids possess a significant intermolecular π···π interaction between COF and the graphene layers of the CNF. As a result, these COF-CNF hybrids (DqTp-CNF and DqDaTp-CNF) exhibit good electrical conductivity (0.25 × 10<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–3<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> S cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">), as well as high performance in electrochemical energy storage (DqTp-CNF: 464 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">). Also, the fabricated, mechanically strong quasi-solid-state supercapacitor (DqDaTp-CNF SC) delivered an ultrahigh device capacitance of 167 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.5 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">. Furthermore, we integrated a monolithic photovoltaic self-charging power pack by assembling DqDaTp-CNF SC with a perovskite solar cell. The fabricated self-charging power pack delivered excellent performance in the areal capacitance (42 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">) at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> after photocharging for 300 s.

Zinc ion interactions in a two-dimensional covalent organic framework based aqueous zinc ion battery - Mohammed, Abdul Khayum; Ghosh, Meena; Vijayakumar, Vidyanand; Halder, Arjun; Nurhuda, Maryam; Kumar, Sushil; Addicoat, Matthew; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Science, 2019)
<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">The two-dimensional structural features of covalent organic frameworks (COFs) can promote the electrochemical storage of cations like H<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, Li<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, and Na<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> through both faradaic and non-faradaic processes. However, the electrochemical storage of cations like Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ion is still unexplored although it bears a promising divalent charge. Herein, for the first time, we have utilized hydroquinone linked β-ketoenamine COF acting as a Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> anchor in an aqueous rechargeable zinc ion battery. The charge-storage mechanism comprises of an efficient reversible interlayer interaction of Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ions with the functional moieties in the adjacent layers of COF (−182.0 kcal mol<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">). Notably, due to the well-defined nanopores and structural organization, a constructed full cell, displays a discharge capacity as high as 276 mA h g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> at a current rate of 125 mA g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">.

Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.

Triazine-based organic polymer-catalysed conversion of epoxide to cyclic carbonate under ambient CO2 pressure - Biswas, Tanmoy; Halder, Arjun; Paliwal, Khusboo S.; Mitra, Antarip; Tudu, Gouri; Banerjee, Rahul; Mahalingam, Venkataramanan (Chemistry-An Asian Journal, 2020)
In this work we have achieved epoxide to cyclic carbonate conversion using a metal-free polymeric catalyst under ambient CO2 pressure (1.02 atm) using a balloon setup. The triazine containing polymer (CYA-ANIS) was prepared from cyanuric chloride (CYA-Cl) and o-dianisidine (ANIS) in anhydrous DMF as solvent by refluxing under the N-2 gas environment. The presence of triazine and amine functional groups in the polymer results in the adsorption of CO2 up to 7 cc/g at 273 K. This inspired us to utilize the polymer for the conversion of a series of functionalised epoxides into their corresponding cyclic carbonates in the presence of tetrabutyl ammonium iodide (TBAI) as co-catalyst. The product has wide range of applications like solvent in lithium ion battery, precursor for polycarbonate, etc. The catalyst was efficient for the conversion of different mono and di-epoxides into their corresponding cyclic carbonates under atmospheric pressure in the presence of TBAI as co-catalyst. The study indicates that epoxide attached with electron withdrawing groups (like, CH2Cl, glycidyl ether, etc.) displayed better conversion compared to simple alkane chain attached epoxides. This is mainly due to the stabilization of electron rich intermediates produced during the reaction (e. g. epoxide ring opening or CO2 incorporation into the halo-alkoxide anion). This catalyst mixture was capable to maintain its reactivity up to five cycles without losing its activity. Post catalytic characterization clearly supports the heterogeneous and recyclable nature of the catalyst.
Keywords: CO2 fixation; cyclic carbonates; epoxides; Heterogeneouscatalyst; metal free catalyst; Triazinepolymer